Leaf and culm silicification of Pampas grass (Cortaderia selloana) developed on different soils from Pampean region, Argentina - Fernández Honaine, Mariana (2017)
Amorphous silica accumulation in grasses is widely described in numerous species; however, work done in relation to the factors affecting this accumulation in the tissues and different type of cells, is still incipient. Here, we analysed a perennial tussock grass, Cortaderia selloana (Schult. & Schult.f.) Asch. & Graebn. (Pampas grass), a native and widely spread species from South America, which is also considered an invasive plant in many regions of the world.Weanalysed the relation between silicification process, soil type and environment, and anatomical features. Silicophytolith content and distribution in plants was analysed through calcination and staining techniques and SEM-EDAX analyses. Silicophytolith content was higher in leaves (2.48–5.54% DW) than in culms (0.29–0.43% DW) and values were similar to other tussock grasses. A relationship between the habit of a grass species and the potential maximum content of amorphous silica is suggested. Plants grown in soils from modified environments with high silica content (Anthrosol and Tecnosol) produced a higher content of amorphous silica. In leaves, the distribution of silicified cells was conditioned by leaf xeromorphic features. Soil Si content and environmental conditions (radiation, disturbance) are more relevant in silicification process than phenological factors. Within leaves, the accumulation of amorphous silica is conditioned by anatomy and transpiration.